2017
DOI: 10.1044/2016_jslhr-l-15-0299
|View full text |Cite
|
Sign up to set email alerts
|

Semantic Processing of Sentences in Preschoolers With Specific Language Impairment: Evidence From the N400 Effect

Abstract: The findings suggest that the neuronal processing of semantic information at sentence level is atypical in preschoolers with SLI compared with TD children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 53 publications
5
32
0
Order By: Relevance
“…Previous studies on unimodal (auditory) semantic integration in children aged between 5-18 years have shown an N400 effect in response to words or pictures that mismatch the preceding context in linguistic priming tasks (e.g. Benau et al, 2011;Holcomb et al, 1992;Pijnacker et al, 2017). Our finding goes beyond unimodal integration by showing that semantic integration does not only occur during information processing of the auditory modality, but is also apparent when information is communicated simultaneously through different modalities.…”
Section: Discussionsupporting
confidence: 54%
“…Previous studies on unimodal (auditory) semantic integration in children aged between 5-18 years have shown an N400 effect in response to words or pictures that mismatch the preceding context in linguistic priming tasks (e.g. Benau et al, 2011;Holcomb et al, 1992;Pijnacker et al, 2017). Our finding goes beyond unimodal integration by showing that semantic integration does not only occur during information processing of the auditory modality, but is also apparent when information is communicated simultaneously through different modalities.…”
Section: Discussionsupporting
confidence: 54%
“…There currently is a lack of research on typically developing school‐aged children and adolescents, ages at which children with language impairments continue to struggle, and a period when the more subtle aspects of semantic and syntactic development continue developing. As a consequence, many studies of Developmental Language Disorder (DLD; also known as Specific Language Impairment) have focused on the earlier stages of development, leading to less information regarding the developmental progression of language comprehension (Haebig, Leonard, Usler, Deevy, & Weber, ; Pijnacker et al, ). This is especially interesting given that some children initially diagnosed with DLD appear to demonstrate close‐to‐normal language skills at later ages (Haebig et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…On the surface, this may be considered surprising, since prior studies have uncovered differences in the size and shape of ERP waveforms elicited in certain clinical populations. For example, children with language disorders demonstrate comparatively reduced (Cummings & Ceponiene, 2010) or delayed (Pijnacker et al, 2017) N400 effects, and similar findings have also been reported for children with dyslexia (Jednoróg, Marchewka, Tacikowski & Grabowska, 2010;Stelmack & Miles, 1990).…”
Section: Discussionsupporting
confidence: 71%